Edukasi Perilaku Hidup Bersih Dan Sehat (PHBS) Dan Latihan Etika Batuk Sebagai Upaya Pencegahan Ispa Di Kelurahan Senalang - Desmawati, Desmawati; Sarapasa, Dwi Rizka Fajriyah; Putri, Elvira Meisiska Dwi; Rupiyanti, Esi; Agustina , Eva; Yunita, Mesfi; Sari, Desmeta (Universitas Dehasen Bengkulu, 2026)
Acute Respiratory Tract Infection (ARI) is a public health problem that remains a major cause of morbidity in Indonesia. Environmental factors, unhealthy lifestyles, and low public knowledge are triggers for the high incidence of ARI. This activity aims to increase public knowledge about ARI through the implementation of Clean and Healthy Living Behavior (PHBS), especially in preventing waste burning and reducing air pollution and implementing coughing and sneezing etiquette training. The method used is health education with a lecture, discussion, and demonstration approach. The results of the activity show an increase in public knowledge after being given education. The implementation of PHBS has proven effective in increasing public awareness of ARI prevention.